GAMBARAN PELAKSANAAN TINDAKAN KEPERAWATAN MENERIMA PASIEN BARU, ORIENTASI PASIEN BARU, PEMENUHAN NUTRISI MELALUI NGT DANMEMBERIKAN OBAT MELALUI NEBULIZER DI RUANG LUKMANUL HAKIM RUMAH SAKIT AL IHSAN BANDUNG - Asmirajanti, Mira (Indonesian Journal of Nursing Health Science, 2016)
AbstractNursing service quality is one of the indicators for assessing the quality of health care ..nursing actions are all actions that nurses do care on behalf of clients. These actions include interventions initiated by a nurse, physician, or collaborative intervention by using standard operating procedures. Standard operating procedures (SOP) is a standard used as a reference in the implementation of an activity or action. SOP is used in this study is the SOP remains in implementing any measures applicable nursing in hospitals Al Ihsan Bandung. Standard operating procedure used consisted of a New Patient Orientation SOP, SOP Accepting New Patients, Fulfillment SOP and SOP Nutrition through NGT Deliver Drugs through Nebulizer.The study design used in this research is descriptive research that aims to obtain a picture of the implementation of nursing actions appropriate operational standards that have been defined. research overview of the implementation of nursing actions: New Patient Orientation, Accepting New Patients, Fulfillment Nutrition through NGT and Deliver Drugs through Nebulizer in Space Lukmanul Hakim Al Ihsan Hospital BandungFrom the results of the assessment from 8-12 February 2010 a new patient admissions process is good enough as many as 75.23% are in accordance with standard operating procedure, and as much as 24.77% which is not in accordance with standard operating procedure relating to patient. Orientation in new patients is not optimal because it just as much as 55.89% of nurses who perform the orientation of the patient in accordance with standard operating procedure is in the room. Giving medicine through Nebulizer is good enough as many as 74.07 is in accordance with standard operating procedure, and as much as 25.03 is not in accordance with the SOP. In action 76.19% of nurses have already done so in accordance with the SOP.A picture that the Implementation Measures of Nursing Accepting New Patients have not been implemented according to the SOP.Â Keywords: Nursing actions, new patients, standard operating procedures